Natural resources for appropriate water treatment - Kebreab Ghebremichael (2006)
The high cost of water treatment has rendered provision of good quality water in the developing world difficult. The search for low-cost treatment options is essential in order to provide safe drinking water. This paper presents a study on the use of Moringa oleifera and pumice as low cost natural materials for improving water treatment systems. Moringa oleifera was found to be very effective for coagulating raw turbid water. The coagulant component was isolated from the seed and purified using a single-step ion exchange purification method. The process was standardized and it can be readily scaled up. The use of pumice for dual media filtration was compared against a mono-medium sand filtration system. In a pilot scale study pumice/sand dual media increased the filter run length two-fold and reduced the volume of backwash water by half.